2015
DOI: 10.2134/cftm2014.0087
|View full text |Cite
|
Sign up to set email alerts
|

Response and Recovery Characteristics of Kentucky Bluegrass Cultivars to Extended Drought

Abstract: During drought, authorities may impose water restrictions for irrigation with little regard for damage to turfgrass. Our objectives were to evaluate the performance of Kentucky bluegrass (Poa pratensis L.) (KBG) cultivars during a prolonged dry down and subsequent recovery in the transition zone near Manhattan, KS, USA. Irrigation was withheld from 30 bluegrasses for 82 days in 2010 and 62 days in 2011. Rainfall was excluded from the study area with an automated rainout shelter. Digital images were collected e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
21
2

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 15 publications
(28 citation statements)
references
References 15 publications
5
21
2
Order By: Relevance
“…Kentucky bluegrass didn't recover from dormancy in any irrigation treatment in either year. This was surprising because KBG typically has good drought tolerance, and previous studies at K-State have indicated it survived extended dry periods well (Lewis et al, 2012;Goldsby et al, 2015). The failure of KBG to survive extended drought in this study may have been related to its being sodded the prior fall, as opposed to the earlier studies in which it has been seeded; more research is needed to investigate this possibility.…”
Section: Resultscontrasting
confidence: 57%
See 1 more Smart Citation
“…Kentucky bluegrass didn't recover from dormancy in any irrigation treatment in either year. This was surprising because KBG typically has good drought tolerance, and previous studies at K-State have indicated it survived extended dry periods well (Lewis et al, 2012;Goldsby et al, 2015). The failure of KBG to survive extended drought in this study may have been related to its being sodded the prior fall, as opposed to the earlier studies in which it has been seeded; more research is needed to investigate this possibility.…”
Section: Resultscontrasting
confidence: 57%
“…The loss of turfgrass during severe droughts may result in unsatisfactory visual appearance and significant reestablishment and human labor costs. Previous studies have indicated that limited water applications during droughts may mitigate the severity of drought stress and improve Kansas State University Agricultural Experiment Station and Cooperative Extension Service the ability of turfgrass to recover upon rewatering (Lewis et al, 2012;Goldsby et al, 2015). This indicates a possible strategy to achieve a balance between water conservation and turfgrass survival through droughty periods.…”
Section: Rationalementioning
confidence: 99%
“…The confidence intervals (α = 0.1) of γ and FTSW t were used to conduct genotypic and species comparisons. Comparing confidence intervals (α = 0.05) used in many studies involving nonlinear regression (Karcher and Richardson, 2008; Richardson et al, 2008; Goldsby et al, 2015) often lead to very conservative results (Schenker and Gentleman, 2001). In our study, α = 0.1 was used to separate more genotypes.…”
Section: Methodsmentioning
confidence: 99%
“…Thus, when extrapolating the data from the relationship between FTSW and gas exchange, it may be important to evaluate other estimates of soil water content to fully elucidate drought resistance mechanisms, including the midpoint of FTSW (FTSW 50 ) at which the response variable declines to 50% of its original value (Sadras and Milroy, 1996). Other limitations in previous studies elucidating mechanisms of drought‐resistant turfgrass cultivars included limited genotypes (Hu et al, 2009; Xu et al, 2011a, 2011b) and a lack of investigation into underlying physiological mechanisms (Richardson et al, 2008; Steinke et al, 2010; Goldsby et al, 2015). A relatively comprehensive study in Australia involving 18 bermudagrass genotypes reported that drought‐resistant genotypes extracted more soil water than drought‐sensitive ones, especially at depths from 50 to 110 cm with lower canopy temperature, higher photosynthetic rate, and relative water content in the leaf.…”
mentioning
confidence: 99%
“…Non-profit organizations such as the National Turfgrass Evaluation Program (Morris & Kenna, 2017;ntep.org), the Turfgrass Water Conservation Alliance (Karlin, 2018; tgwca.org, TWCA), and the Alliance for Low-Input Sustainable Turf (Husen, 2018; a-listturf.org) have been founded with the mission to evaluate and promote turfgrasses that require less water under drought-stress conditions using stringent evaluation protocols (Hignight et al, 2019;Hunsen, 2018). Extensive research, utilizing these protocols on mature turfgrasses, has identified many improved, drought-resistant turfgrass cultivars (Bushman et al, 2012;Goldsby et al, 2015;Karcher et al, 2008;Richardson et al, 2008Richardson et al, , 2009. It is unknown if cultivars exhibiting enhanced genetic drought resistance at maturity might also demonstrate improved establishment under deficit-irrigation conditions.…”
mentioning
confidence: 99%